153k views
3 votes
Multiply (3x – 1)(5x – 9)

User Ruchan
by
6.1k points

1 Answer

4 votes

According to the distributive property, multiplying the sum of two or more addends by a number will give the same result as multiplying each addend individually by the number and then adding the products together.


(a+b)\cdot c=a\cdot c+b\cdot c

Using this property in our problem, we have:


\begin{gathered} (3x-1)(5x-9)=3x(5x-9)-1(5x-9) \\ =(3x)\cdot(5x)+(3x)\cdot(-9)+(-1)\cdot(5x)+(-1)\cdot(-9) \\ =15x^2-27x-5x+9 \\ =15x^2-32x+9 \end{gathered}

User Alex Kolarski
by
6.0k points